Unraveling Origin, History, Genetics, and Strategies for Accelerated Domestication and Diversification of Food Legumes - Ambika,; Aski, Muraleedhar S.; Gayacharan,; Hamwieh, Aladdin; Talukdar, Akshay; Kumar Gupta, Santosh; Sharma, Brij Bihari; Joshi, Rekha; Upadhyaya, H. D.; Singh, Kuldeep; Kumar, Rajendra (Frontiers in Genetics, 2022)
Domestication is a dynamic and ongoing process of transforming wild species into cultivated species by selecting desirable agricultural plant features to meet human needs such as taste, yield, storage, and cultivation practices. Human plant domestication began in the Fertile Crescent around 12,000 years ago and spread throughout the world including China, Mesoamerica, the Andes and Near Oceania, Sub-Saharan Africa, and eastern North America. Indus valley civilizations have played a great role in domestication of grain legumes. Crops such as pigeonpea, blackgram, greengram, lablab bean, mothbean and horse gram are originated in Indian subcontinent, and Neolithic archeological records indicates that these crops were first domesticated by early civilizations in the region. Domestication and evolution of wild ancestors into today's elite cultivars are important contributors to global food supply and agricultural crop improvement. In addition, food legumes contribute to food security by protecting human health and minimize climate change impacts. During the domestication process, legume crop species have undergone a severe genetic diversity loss, and only a very narrow range of variability is retained in the cultivars. Further reduction in genetic diversity occurred during seed dispersal and movement across the continents. In general, only a few traits such as shattering resistance, seed dormancy loss, stem growth behaviour, flowering-maturity period, and yield traits have prominence in the domestication process across the species. Thus, identification and knowledge of domestication responsive loci were often useful in accelerating new species' domestication. The genes and metabolic pathways responsible for significant alterations that occurred as an outcome of domestication might aid in the quick domestication of novel crops. Further, recent advances in “omics” sciences, gene editing technologies and functional analysis will accelerate the domestication and crop improvement of new crop species without losing much genetic diversity. In this review, we have discussed about the origin, centre of diversity and seed movement of major food legume crops, which will be useful in exploration and utilization of genetic diversity in crop improvement. Further, we have discussed about the major genes/QTLs associated with the domestication syndrome in pulse crops and the future strategies to improve upon the food legume crops.